2010
DOI: 10.1126/science.1194662
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Iron in Earth’s Inner Core

Abstract: Earth's solid inner core is mainly composed of iron (Fe). Because the relevant ultrahigh pressure and temperature conditions are difficult to produce experimentally, the preferred crystal structure of Fe at the inner core remains uncertain. Static compression experiments showed that the hexagonal close-packed (hcp) structure of Fe is stable up to 377 gigapascals and 5700 kelvin, corresponding to inner core conditions. The observed weak temperature dependence of the c/a axial ratio suggests that hcp Fe is elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
269
5
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(306 citation statements)
references
References 27 publications
29
269
5
3
Order By: Relevance
“…In order to interpret seismic data and build geophysical models, 4 knowing the core composition and structure is of high priority. It is generally to 380 GPa and 5700 K (Tateno et al, 2010), whilst increasing temperature 14 at moderate pressure has been shown to stabilise an fcc phase (Lin et al,15 2002). The fcc phase was also found to be stabilised by increased Ni con-16 tent (Mao et al, 2006;Kuwayama et al, 2008) at temperatures up to 3500 17 K and pressures of 200 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to interpret seismic data and build geophysical models, 4 knowing the core composition and structure is of high priority. It is generally to 380 GPa and 5700 K (Tateno et al, 2010), whilst increasing temperature 14 at moderate pressure has been shown to stabilise an fcc phase (Lin et al,15 2002). The fcc phase was also found to be stabilised by increased Ni con-16 tent (Mao et al, 2006;Kuwayama et al, 2008) at temperatures up to 3500 17 K and pressures of 200 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the c/a-ratio has been previously 81 been found rather insensitive to temperature (Tateno et al, 2010). In or-82 der to limit the computational burden in our alloy configuration calculations 83 (Sections 3.1 and 3.2), we therefore used equilibrium c/a-ratios obtained at 84 T = 0 K and P = 0 GPa also at elevated temperature and pressure for our 85 studies of mixing enthalpy and short-range order.…”
mentioning
confidence: 99%
“…However, the FE calculation is based on integration from low temperature, and it is necessary that a harmonic treatment be appropriate there for the method (in the basic form presented here) to be applicable. For the demonstration, we calculate the absolute FE of the high-pressure hcp phase of iron (which is a candidate structure in the Earth's inner core 49 ) for a single isochore (7.0Å 3 /atom) up to temperatures near melting (5000 K), with full inclusion of anharmonicity, electronic excitation, and the change of equilibrium c/a ratio with temperature. At the conditions of interest, iron is paramagnetic, and we neglect contributions to the FE from magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering powder X-ray diffraction experiments have now reached the extreme conditions of the inner core 10 . But much work remains to identify the exact composition of the iron alloy in the core and how its crystal structure and physical properties connect to the seismic observations.…”
Section: Core Puzzlesmentioning
confidence: 99%